Population dynamics and trophic interactions of Atlantic cod along the Greenland shelf - Werner, Karl-Michael (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2020)
This thesis deals with trophic interactions and population dynamics of Atlantic cod along the Greenland shelf. Here, the cod stock experienced decade-long overfishing and at the same time the most important food source, capelin, fluctuated in abundance. In my thesis I showed, how trophic interactions and habitat choice affect body condition of cod and how this might have contributed to the decline of the stock. The thesis attempts to synthesize, how these findings can be integrated in an ecosystem-based management. Diese Dissertation handelt von trophischen Interaktionen und Populationsdynamiken des Kabeljau entlang des Grönlandschelf. Hier wurde der Kabeljau jahrzehntelang überfischt und zur selben Zeit fluktuierte sein wichtigster Beutefisch, die Lodde. In meiner Dissertation habe ich gezeigt, wie trophische Interaktionen und Habitatwahl die körperliche Verfassung vom Kabeljau beeinflussen und wie dies zum Kollaps des Bestandes beigetragen haben könnte. Die Dissertation hat das Ziel herauszustellen, wie diese Erkenntnisse zu einem ökosystembasierten Management beitragen können.